The Application of Contextual Approach in PAI Learning in Shaping Adolescent Morals at MTS Ainul Yaqin Wonomerto Probolinggo - Andi, M Andika Dika; Nuha, Nazah Ulin (FALASIFA : Jurnal Studi Keislaman, 2025)
This study aims to measure the effectiveness of contextual-based Islamic religious education in shaping the morals and character of students at MTs Ainul Yaqin, as well as to understand the role of teachers and the impact of family environment on student behavior. Through this approach, students are expected to internalize Islamic values in their daily lives, overcome the negative impacts of globalization, and strengthen their morality. The study employs a qualitative method with a descriptive approach, where data is collected through interviews, observations, and case studies at MTs Ainul Yaqin Wonomerto, Probolinggo Regency, focusing on the analysis of everyday phenomena related to contextual-based learning. The results indicate that the implementation of contextual-based Islamic religious education has proven effective in shaping students' morals, as evidenced by significant improvements in behaviors such as honesty, responsibility, and discipline, along with students' ability to apply religious values in real life, which also enhances their motivation to learn more actively and engage more deeply